Introduction to Applied Linear Algebra : Vectors, Matrices, And Least Squares - Boyd, Stephen P., author; Vandenberghe, Lieven, author (Cambridge, UK ; New York, NY : Cambridge University Press, 2018)
Includes bibliographical and references